Glamour : women, history, feminism - Dyhouse, Carol (Zed Books, 2010)
Glamour: Women, History, Feminism explores the changing meanings of the word glamour, its relationship to femininity and fashion, and its place in twentieth-century social history. Using a rich variety of sources from women's magazines and film, to social surveys and life histories Carol Dyhouse examines with wit and insight the history and meaning of costume, cosmetics, perfume and fur.
Keywords: Women's clothing : Social aspects : 20th century; Women : Social conditions : 20th century; Beauty, Personal : Social aspects : 20th century; Aesthetics, Modern; Feminine beauty (Aesthetics) : 20th century; Fashion : Social aspects : 20th century; Glamour : History : 20th century; Gender studies: women